Kontribusi Pelaksanaan Ritual Hindu Terhadap Kesempatan Kerja Dan Kesejahteraan Masyarakat Di Kabupaten Badung Provinsi Bali (Studi Kasus Mlaspas Dan Ngenteg Linggih Di Pura Pasek Preteka Desa Abiansemal) - Sunariani, Ni Nyoman; Sukarsa, Made; Sri Budhi, Made Kembar; Marhaeni, AAIN. (Jurnal Ekonomi Kuantitatif Terapan; 2014: Vol. 7, No. 2, Agustus 2014 (pp. 83-198), 2015)
The aim of this research is to know the benefits of rituals Hinduism religion from the social, cultural, and economic perspective, the magnitude of multiplier effects; increasing income and the influence of rituals on the community welfare either directly or indirectly through employment opportunities in Bali. Research case study the ritual Mlaspas and Ngenteg Linggih in the village of Abiansemal is to refute the phenomenon that develops in society that of rituals Hinduism in Bali that ineffective and inefficient. Sample is the family head temple and suppliers material ritual. Collecting cross-sectional primary data through in-depth interviews with key and expert informants and triangulation. Descriptive analysis method of analysis and techniques used in this research is goodness-of-fit criteria which used in the analysis of structural equation a modelling (SEM) and a causal relation between of variable latent tested by using significant test in statistika. Next the result showed that the implementation of ritual besides well-functioned religious also a positive impact on social, culture, and the economy. Ritualistic Hinduism has a multiplier effect of 2.37, thus increasing the additional revenue of suppliers amounting to 72.06 percent. And Implementation of rituals had positive and significant impact on the welfare of the people, either directly or indirectly through employment opportunities as a stimulus and acceleration of economic growth to improve the welfare of people Abiansemal sub-district in particular, and Bali in general.
Keywords: Implementation of the ritual; the multiplier effect; employment opportunities; community welfare